Development of a method for the preparation of zirconium-89 radiolabelled chitosan nanoparticles as an application for leukocyte trafficking with positron emission tomography. (December 2017) - Fairclough, M.; Ellis, B.; Boutin, H.; Jones, A.K.P.; McMahon, A.; Alzabin, S.; Gennari, A.; Prenant, C.
Abstract: Positron Emission Tomography is an attractive imaging modality for monitoring the migration of cells to pathological tissue. We evaluated a new method for radiolabelling leukocytes with zirconium-89 ( 89 Zr) using chitosan nanoparticles (CN, Z-average size 343 ± 210 nm and zeta potential +46 ± 4 mV) as the carrier. We propose that cell uptake of 89 Zr-loaded CN occurred in a two-step process; cell membrane interaction with 89 Zr-loaded CN was followed by a slower cell internalisation step. Highlights: Zirconium-89 radiolabelled chitosan nanoparticles prepared for cell labelling. Uptake and efflux of zirconium-89 chitosan nanoparticles studied in leukocyte cells. Two step cell uptake mechanism proposed.